Water body restoration and development - A case study of Askar Dighi Water Tank of Chittagong - Shahjahan, A T M; Chowdhury, Panini Amin; Ali, Mohd Mostakim (Journal of Bangladesh Institute of Planners, 2015)
Askar dighi is a very old water tank of Chittagong, which is now encroached by illegal settlements, and because of the waste dumping activities, its water quality has degraded at a severe level. Although creation of a recreational zone is a crying need for Chittagong, no one pays any attention for utilizing the potential of this majestic dighi. The main objective of this study is to develop some ideas to turn this dighi into a recreational place, followed by designs and a draft budget plan. Improvement of the recreational facilities in the port city is a dying need to restore its heritage and culture. By reviewing various articles and projects, this paper formulates a strategic plan to restore this dighi for the best possible use. A budget plan is developed considering the present day costs and an earning and management strategy is also prepared for this project. GIS Based secondary data and field level primary data has been collected and used for the research. If the improvement plan is executed, the city will not only get a natural recreational open space, but also, it will be a big step forward for sustainable city development. Thus in future, it can be a symbol of glory for the city and a place for healthy living for the urban dwellers. Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 203-208